2018
DOI: 10.1152/ajprenal.00314.2017
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin reduces plasma uremic toxins and alters the intestinal microbiota composition in a chronic kidney disease mouse model

Abstract: Accumulation of uremic toxins, which exert deleterious effects in chronic kidney disease, is influenced by the intestinal environment; the microbiota contributes to the production of representative uremic toxins, including p-cresyl sulfate and indoxyl sulfate. Canagliflozin is a sodium-glucose cotransporter (SGLT) 2 inhibitor, and it also exerts a modest inhibitory effect on SGLT1. The inhibition of intestinal SGLT1 can influence the gastrointestinal environment. We examined the effect of canagliflozin on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 59 publications
2
76
2
1
Order By: Relevance
“…Thus, given at high doses, canagliflozin may serve as a dual SGLT1/2 inhibitor and have both direct and indirect effects related to blocking intestinal SGLT1. Further supporting this, canagliflozin significantly increased cecal short‐chain fatty acids (SCFA) in mice with CKD, suggesting increased bacterial carbohydrate fermentation in the intestine . Of note, canagliflozin's SGLT1 inhibitory action might not only be found in the intestine.…”
Section: Intestinal Sglt1 Inhibition: What Does It Add?mentioning
confidence: 79%
See 1 more Smart Citation
“…Thus, given at high doses, canagliflozin may serve as a dual SGLT1/2 inhibitor and have both direct and indirect effects related to blocking intestinal SGLT1. Further supporting this, canagliflozin significantly increased cecal short‐chain fatty acids (SCFA) in mice with CKD, suggesting increased bacterial carbohydrate fermentation in the intestine . Of note, canagliflozin's SGLT1 inhibitory action might not only be found in the intestine.…”
Section: Intestinal Sglt1 Inhibition: What Does It Add?mentioning
confidence: 79%
“…Surprisingly, treatment with a dual SGLT1/2 inhibitor did not affect relative abundance of bacterial orders or bacteria of interest in diabetic rodents . In contrast, in an adenine‐induced CKD mouse model, 2‐week canagliflozin treatment significantly altered microbiota composition in CKD mice . More studies are needed to better understand the role of SGLT1 and/or 2 inhibition on changes in gut microbiota.…”
Section: Intestinal Sglt1 Inhibition: What Does It Add?mentioning
confidence: 95%
“…The latter may augment glucose exposure of the colonic microbiota and formation of metabolites (11). It has been shown that canagliflozin altered the intestinal microbiota composition in mice with chronic kidney disease (12). The effects of dapagliflozin on fecal microbiota remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании канаглифлозина по влиянию на кишечную микробиоту у животных с нарушением функции почек в группе приема препарата отмечалось увеличение КЦЖК в толстом кишечнике. При анализе микробного состава толстого кишечника не было выявлено значительной разницы в соотношении Firmicutes/Bacteroidetes, однако на уровне родов наблюдалось снижение количества Actinobacteria, Bifidobacterium и Oscillospira по сравнению с контрольной группой [51].…”
Section: влияние инкретиновunclassified